The Association of TNF-Alpha Inhibitors and Development of IgA Nephropathy in Patients with Rheumatoid Arthritis and Diabetes. (21st April 2020) - Premužić, Vedran; Padjen, Ivan; Cerovec, Mislav; Ćorić, Marijana; Jelaković, Bojan; Anić, Branimir
Abstract : IgA nephropathy (IgAN) is a rather uncommon complication of TNF-alpha inhibition with a range of findings such as asymptomatic microscopic/macroscopic hematuria or different degrees of proteinuria and could progress to end-stage renal disease. We are reporting three patients with longstanding rheumatoid arthritis (RA), which developed IgAN while receiving TNF-alpha inhibitors. All off our three patients had RA, which lasted 2–4 years, and none of them had a prior history of chronic kidney disease. Two patients were treated with adalimumab while one patient was treated with golimumab. Discontinuation of anti-TNF-alpha therapy and initiation of immunosuppressive therapy led to improvement in serologic abnormalities and renal function in two patients, while the third patient's 24-hour proteinuria was only partially reduced, which supports previous reports on TNF-alpha inhibitor induced autoimmunity. Two of our patients had previously been diagnosed with type 2 diabetes mellitus while the third patient developed diabetes years after the onset of IgAN. This is in line with the previously described association of IgAN and diabetes mellitus. To our best knowledge, this is the first report to analyze the development of IgAN as a potential consequence of anti-TNF-alpha therapy and its possible association with pretreatment or posttreatment diabetes.